Hisse Senedi Fiyatlarının Modellenmesi ve Opsiyonların Fiyatlandırılması: Binomial Yaklaşım - (:unkn) unknown (My University, 2002)
0

In this study, we explain to the pricing hedging of derivatives in finite markets models. In this setting we work out of the key financial and mathematical ideas underlying modern derivatives. Asset analysis without having to deal with the technicalities stochastic calculus. We explain the notation of dynamic edging and introduce the concept of an equivalent martingale - measure. We discuss the fundamental theorem of asset pricing and derive the Risk- Neutral pricing principle. To illustrate these concepts we briefly discuss the Binomial model of Cox, Ross and Rubinstein (1979)